Pengelolaan Sistem Informasi Karya Ilmiah - Ulum, Amirul; Budiwijaya, M.N. (Pustakaloka, 2012)
Today, many libraries such as academic library have developed local digital repositories. A significant increase in the development of repositories is expected with technology and process improvements for digital collection development. Current information technology requires interoperabilty between systems that facilitate the exchange of data and information. Use of the web based applications and data through oen archives initiative (OAI) protocol or the other systems can be a bridge to access the local digital collection. this study discusses about the implementation of information systems using free software eprints. The result is an Eprints can be used its an information system for institutional repositories that has interoperability with other system.